Drivers of autonomous vehicles' acceptance: examination of influential factors for intention to buy and use autonomous vehicles - Reis, Carolina Mendes dos (2021)
The implementation of autonomous vehicles (AVs) can generate a variety of positive outcomes to the society. However, the technology has to be accepted by the population first. Therefore, the objective of this work is to explore which factors influence public acceptance of privately owned and shared AVs. Based on a sample of 383 respondents from the city of Lisbon, it can be documented that young and well educated male respondents who live in urban and suburban areas represent the group with higher intention to buy and use AVs in the future. They also represent the group with higher WTP for AVs. Positive attitude towards shared mobility services is a positive predictor of shared AV usage, along with the levels of awareness and perceived benefits. Perceived concerns, on the other hand, are negative predictors of willingness to use, buy and pay for AVs.